GE_GERICHTE P/9042/2025 vom 16. April 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;VIOLATION DU SECRET PROFESSIONNEL(DROIT PÉNAL);CONSENTEMENT DU LÉSÉ | CPP.310.al1.leta; CP.321